FENOMENA BOROH DI PADANGSIDIMPUAN DALAM PERSPEKTIF FIQH MUAMALAH - Dasopang, Nur Sania (Jurnal Ilmiah Ekonomi, Manajemen dan Syariah, 2023)
The phenomenon that occurs in the people of North Sumatra, especially the Padangsidimpuan area is the practice of "Boroh" where people make loans by providing land/personal belongings as collateral where the collateralized land/goods are fully controlled by the creditor until the debt is paid off. The large number of people doing this practice is not without reason, because the "Boroh" practice is the most real solution to solving one's economic problems without having to borrow from a bank at interest, and also having to provide collateral for assets to get loan approval at a bank.   The purpose of this study is to see how the influence of the Islamic stock market on investment and economic growth in Indonesia.The purpose of this research is to find out the Fiqh Muamalah perspective on Boroh practices that are entrenched in the Padangsidimpuan community and to classify Boroh transactions.This type of research is descriptive qualitative. In this study, the case studied is the phenomenon of boroh transactions that occur in the people of the city of Padangsidimpuan, North Sumatra. In this research, the approach used is Case Study and Document Study. Fiqh Muamalah views Boroh transactions as transactions that are prohibited in Islam. The Boroh transaction that occurred in the Padangsidimpuan community has its own position in lending and borrowing because it does not have a clear maturity contract.